The green mile [videorecording (DVD)] - Valdes, David; Darabont, Frank; Darabont, Frank; Hanks, Tom; Morse, David, 1953-; Hunt, Bonnie; Duncan, Michael Clarke; Cromwell, James; Jeter, Michael, 1952-2003; Greene, Graham, 1952-; Hutchison, Doug, 1960-; Rockwell, Sam; et al. (2006)
"Miracles happen in unexpected places, even on death row at Cold Mountain Penitentiary. There John Coffey, a prisoner with supernatural powers, brings a sense of spirit and humanity to his guards and fellow inmates"--Container.